The emergence of an ethic of care in rural Kenyan schools? Perspectives of teachers and orphaned and vulnerable pupils. Issue 2 (4th March 2017) - Skovdal, Morten; Evans, Ruth
Abstract : In the context of HIV, there is considerable debate about the role of schools and teachers as potential sources of care and support for vulnerable children. This qualitative research examines 'care' as experienced and practiced by pupils and teachers in rural Western Kenya. In primary and secondary schools, interviews were conducted with 18 teachers and 57 orphaned and vulnerable pupils, alongside Photovoice. Drawing on thematic analysis and an 'ethic of care' theoretical perspective, we unpack the informal caring practices of teachers within resource-constrained settings. The research provides glimpses of schools as spaces of care, participation and support for orphaned and vulnerable pupils. Recognising and providing institutional support for the development of an ethic of care in schools may help to tackle the considerable educational barriers facing girls and boys who are orphaned and vulnerable and move 'care' closer towards the centre of educational policy and practice in the global South.